2015
DOI: 10.1055/s-0034-1396241
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperuricemic and Nephroprotective Effects of Rhein in Hyperuricemic Mice

Abstract: Hyperuricemia has been considered to be a key risk factor for kidney disease. The formation of uric acid crystals in the kidney further stimulates an intensive inflammatory response. Rhein possesses various pharmacological activities, including anti-inflammatory, antioxidative, antitumor, purgative effects, and so on. To our knowledge, no previous work has been reported about the therapeutic effect of rhein on urate nephropathy. In this study, a model of hyperuricemia and nephropathy induced by adenine and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Our results are consistent with Meng et al [ 44 ] who reported that rhein possesses various pharmacological activities, including anti-inflammatory, antioxidant, and antitumor. In their study, a model of hyperuricemia and nephropathy induced by adenine and ethambutol in mice was established.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with Meng et al [ 44 ] who reported that rhein possesses various pharmacological activities, including anti-inflammatory, antioxidant, and antitumor. In their study, a model of hyperuricemia and nephropathy induced by adenine and ethambutol in mice was established.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the increased activity of XO may also be an indirect measurement of serum uric acid level. Recently, association between hyperuricaemia and renal failure has also been reported (Meng et al, ; Ohashi et al, ). In addition, the observable reduction in both renal and cardiac NO also contributed significantly to the development of hypertension.…”
Section: Discussionmentioning
confidence: 91%
“…Again, the increased serum activity of XO has been associated with oxidative stress through generation of ROS [54] and is also an indirect measurement of serum uric acid level [27] . Meng et al [55] and Ohashi et al [56] recently suggested a link between hyperuricaemia and renal failure which is a possibility following SMV exposure.…”
Section: Discussionmentioning
confidence: 99%